Tahap dialog peradaban di kalangan pelajar-pelajar tahun 3, UTM Skudai - Suratman, Azmi Shah; Ripin, Mohd. Nasir; Awang, Ramli; Sayed Ahmad, Sayed Mahussain; Haron, Zulkifli (UTM, 2003)
The objective of this research is to examine and to indentify the level of civilizational dialogue among 3rd year students of Universiti Teknologi Malaysia (UTM). This research is focusing on the respondents culture of interaction and dialogue, honesty and values of concern and an attitude of tolerance among the students. This is a descriptive study using questionnaire containing 27 items using Likert Scale 1 to 4. It has been distributed to 467 respondents among 3th year students from various Faculty in Universiti Teknologi Malaysia, and analysized using Statistical Package For Social Science (SPSS) 11.5 for Windows to get the frequency, percentage and mean which is presented in a table form. Overall outcome of this research shows that the level of score is average, however values of concern and the level of tolerance are high. This high level score could be improved with the suggestion has been presented in this research. In future, university management could organize more programs on civilizational dialogue among this student of University Technology of Malaysia. In general it was found that the foundation of civilizational dialogue among the respondents are strong. Nurturing and motivating towards upgrading the programs and internalization of civilizational dialogue should be continously developed. All the effots in promoting the dialogue should be supported by various layer of society especially the leaders.